Association between menarche age and menstrual disorder with the incidence of uterine fibroid in medan, Indonesia: based on hospital data - Ganis Siregar, Muhammad Fidel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine fibroids are benign, monoclonal tumors of the smooth muscle cells found in the human uterus. The incidence of uterine fibroid in Indonesia is between 2.39% - 11.7% in all gynecology inpatient. Despite the fact that their cause is still unknown, there is considerable evidence that estrogens and progestogens proliferate tumor growth, as the fibroids rarely appear before menarche and regress after menopause. Methods: An observational analytic study with case control approach. Total sample from this study was 498 people, with 249 cases and 249 controls. The samples were collected through purposive sampling. The study was conducted in the medical record division of Adam Malik General Hospital Medan. Results from the study were analyzed with chi square. Results: The result of this study demonstrated an association between menarche age with uterine fibroid incidence, with a p-value < 0.05, and odds ratio = 2.487 (CI 1.585-3.902). This indicate that the incidence of uterine fibroid is 2.5 greater in women with menarche age of < 10 years old. P-value < 0.05 and odds ratio = 0.258 (CI 0.178-0.375) were obtained from the association between menstrual disorder and uterine fibroid incidence. Conclusions: The result of this study demonstrates a significant association correlation between menarche age and the development of uterine fibroid. Early menarche age increases risk of uterine fibroid incidence, whereas menstrual disorder is more likely a clinical manifestation of uterine fibroid, rather than a risk factor.